ATI TEAS 7 study guide 2023-2024 : 4 practice exams and TEAS test review book for nursing entrance - Rueda, Joshua (TPB Publishing, 2023)
This study guide contains several key sections that will help you be successful on your exam. The guide contains tips for what you should do the night before and the day of the test. Also included are test-taking tips. These tips will help equip you to accurately read, assess, and answer test questions. The guide is devoted to showing you what content to expect on the exam and to helping you better understand that content. In this guide are practice test questions so that you can see how well you have grasped the content. The answer explanations will help you to learn from your mistakes and overcome them.